LONG-TERM REGIONAL FORECASTE AND MAPPING OF NATURAL REGIME OF GROUNDWATER LEVELS (ON EXAMPLE OF AREAS OF SOME ADMINISTRATIVE REGIONS) - Davybida, L. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The method of long-time regional forecasting natural hidroheodynamic regime are given. The results of the proposed algorithm are presented for areas with different conditions of formation of level regime. Areas of homogeneous multi-mode variability of groundwater levels are selected within the studied regions. The most likely periods of high water content are determined and the corresponding mapping model predictive sufficiency levels are built.